Short-term impacts of COVID-19 on the Malawian economy: Initial results - Baulch, Bob; Botha, Rosemary; Pauw, Karl (International Food Policy Research Institute, 2020)
This Report describes the initial results of modeling undertaken by IFPRI to assess the short-run impacts of the COVID-19 control measures on the Malawian economy. We also consider the short-run effects of external shocks associated with disruptions in trade, investment, and remittance flows on the Malawian economy, as well as two medium-term paths assuming either faster or slower recovery during the remainder of 2020. This analysis has been undertaken in order to inform the policy response to the COVID-19 pandemic in Malawi and represents a first pass attempt to measure the short-term economic impacts of COVID-19 on the Malawian economic. It should be noted that, unlike NPC (2020) our estimates of the economic impact of the COVID-19 on the Malawian economy do not extend beyond 2020 and do not try to set a value on loss of life or life-years. They do, however, allow for detailed breakdown of the direct and indirect impacts of COVID-19 on different sectors and sub-sectors of the Malawian economy.